2014
DOI: 10.4149/bll_2014_109
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of polymorphisms in CYP2C9 and VKORC1 genes influencing warfarin metabolism in Slovak population: implication for clinical practice

Abstract: Objectives: The study was aimed at establishing an effective molecular-genetic method for detecting polymorphisms in genes CYP2C9 and VKORC1, which affect the pharmacogenetics of warfarin, and at determining their prevalence in Slovak population. Background: Warfarin, derivative of coumarin, belongs to the most commonly prescribed oral anticoagulants with narrow therapeutic index. An insuffi cient dose of warfarin can result in failure to produce the antithrombotic effect, whereas an overdose increases the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
5
0
3
Order By: Relevance
“…have demonstrated that there is a strong association between CYP2C9 variant alleles and warfarin dose requirement . After that, many studies have certified the significant effect of CYP2C9 on warfarin doses in adult patients . Moreover, a dosing algorithm for adult patients has been established by the US Food and Drug Administration and International Warfarin Pharmacogenetics Consortium .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have demonstrated that there is a strong association between CYP2C9 variant alleles and warfarin dose requirement . After that, many studies have certified the significant effect of CYP2C9 on warfarin doses in adult patients . Moreover, a dosing algorithm for adult patients has been established by the US Food and Drug Administration and International Warfarin Pharmacogenetics Consortium .…”
Section: Introductionmentioning
confidence: 99%
“…5 After that, many studies have certified the significant effect of CYP2C9 on warfarin doses in adult patients. [6][7][8][9][10][11] Moreover, a dosing algorithm for adult patients has been established by the US Food and Drug Administration and International Warfarin Pharmacogenetics Consortium. 1,2 However, due to several factors,the pharmacogenetic model for adults cannot be directly used for pediatric patients, and need for pediatric-focused pharmacogenomic studies.…”
mentioning
confidence: 99%
“…Products of two important genes, VKORC1 (vitamin K epoxide reductase complex subunit 1) and CYP2C9 , are responsible for the majority of the pharmacodynamics and pharmacokinetics of warfarin, respectively (Farzamikia et al, 2018[ 12 ]; Wu, 2018[ 49 ]). Firstly, warfarin is metabolized by the hepatic CYP2C9 enzyme and then inhibits the coagulation cascade through the targeting of the VKORC1 enzyme to decrease the active vitamin K regeneration from vitamin K epoxide (Krajciova et al, 2014[ 21 ]; Sridharan et al, 2016[ 41 ]).…”
Section: Introductionmentioning
confidence: 99%
“…There is overwhelming evidence that single nucleotide polymorphisms (SNPs) in the CYP2C9 and VKORC1 genes are strongly associated with variability in dose requirements and occurrence of bleeding complications during warfarin treatment (Jones and Miller, 2011[ 18 ]; Relling and Evans, 2015[ 34 ]). Various studies showed that VKORC1 (−1639G>A) rs9923231 polymorphism may cause or be associated with up to forty percent of the dose variation in some populations and, in comparison with the wild type, individuals carrying this polymorphism showed lower warfarin requirements (Krajciova et al, 2014[ 21 ]; Bader and Elewa, 2016[ 4 ]).…”
Section: Introductionmentioning
confidence: 99%
“…PCR amplifi cations were performed in 20-μl reaction volumes containing 150-200 ng of genomic DNA (1 μl), PCR Master Mix (2x) Fermentas (Waltham, Massachusetts USA) (10 μl), 0.5 μM (1 μl) of each primer (Sigma-Genosys, Lambda Life, Slovakia) and nuclease free water to a total volume of 20 μl (29).…”
Section: Methodsmentioning
confidence: 99%